Breaking the circle of commercial sex workers - Moiloa, Tau Zacharia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2009.